Professional dialogues in the early years : rediscovering early years pedagogy and principles - Wild, Mary; Alexander, Elise; Briggs, Mary; Gilson, Catharine; Lake, Gillian; Mitchell, Helena; Swarbrick, Nick (Critical guides for teacher educators., 2018)
This book provides early years teacher educators with critical guidance to explore the enduring philosophies and principles of early years' pedagogy and to creatively interpret and communicate these to those they are training to be teachers and professionals.